Blocking connexin43 hemichannels prevents TGF‐β2 upregulation and epithelial–mesenchymal transition in retinal pigment epithelial cells. (9th November 2021) - Lyon, Heather; Yin, Naibo; Rupenthal, Ilva D.; Green, Colin R.; Mugisho, Odunayo O.
Abstract: Epithelial–mesenchymal transition (EMT) occurs when polarised epithelial cells change to a mesenchymal phenotype. EMT plays a role in several chronic conditions, including ocular diseases with retinal pigment epithelium (RPE) EMT associated with retinal diseases such as diabetic retinopathy (DR). Here, EMT results in breakdown of the blood‐retinal barrier (BRB) leading to sub‐retinal fluid deposition and retinal detachment. Previous studies have shown that blocking connexin43 (Cx43) hemichannels can protect against RPE BRB breakdown, but the underlying mechanism is unknown. To determine whether open Cx43 hemichannels may enable EMT of RPE cells and thus result in BRB breakdown, ARPE‐19 cells were either challenged with high glucose plus the inflammatory cytokines IL‐1β and TNF‐α (HG + Cyt) to simulate DR or treated with the Cx43 hemichannel blocker tonabersat alongside the HG + Cyt challenge. HG + Cyt induced a morphological change in RPE cells to a fibroblastic phenotype with a corresponding decrease in epithelial zonular occludens‐1 and an increase in the fibroblastic marker α‐SMA. The HG + Cyt challenge also induced loss of transepithelial electrical resistance while increasing dye passage between RPE cells. All of these changes were significantly reduced with tonabersat treatment, which also prevented HG + Cyt‐induced transforming growth factor‐β2 (TGF‐β2) release. In conclusion, Cx43 hemichannel block with tonabersat attenuated both TGF‐β2 release and RPE EMT under disease‐mimicking conditions, offering the potential to ameliorate the progression of EMT‐associated retinal diseases.